Polyiminopyridines based networks as supports to heterogenize iron(II) complexes. Application as efficient and selective ecofriendly catalysts. Issue 3 (4th March 2016) - Maya, Eva M.; Verde‐Sesto, Ester; de la Campa, José G.; Iglesias, Marta
Abstract: A series of polyiminopyridines (PIPys ) were reported and used as supports to prepare heterogenized‐iron catalysts (FePIPys ). The resultingPIPys exhibit moderate surface areas (SBET ≈ 200 m 2 g −1 ) and high chemical and thermal stability. The catalytic performance ofFePIPys–catalyts was studied in the acetalization of furfural and 5‐hydroxymethyl furfural to yield compounds of potential interest as diesel additives. The structure of the polyiminopyridine support has great influence in the catalytic performance and recyclability; all catalysts maintained the activity and the selectivity after several cycles. Abstract : Synthesis and characterization of polyiminopyridines (PIPys) and their corresponding iron heterogenized catalysts (FePPys). The catalysts were tested in the acetalization of furfural and 5‐hydroxymethyl furfural showing excellent conversions and selectivity toward the acetal derivatives using only 0.1 w% of catalysts (based on Fe) and short reaction times. The catalysts were recyclable maintaining their catalytic activity.